Extension of the UTAUT Model: Assessing the Impact of Consumers’ Financial Literacy on Intention to Adopt Cryptocurrency Platforms in India - Khan, Khushnuma; Khan, Matloob Ullah; Gupta, Neha; Gulyani, Garishma; Singh, Poonam; Rasool, Ishrat; Nisa, Syeedun (International Journal of Economics and Financial Issues, 2024)
In this research paper, we investigate the variables that impact the behavioural intention of cryptocurrency investors in India. The analysis of the data was done using smart partial least square-structural equation modelling. The study was carried out in India using purposive sampling and included investors who had a fundamental understanding of cryptocurrency. It has been established that factors such as financial literacy, facilitating conditions, social influence, effort expectancy and performance expectancy have a significant influence on the investment behaviour of these individuals. The study looks at how the Unified Theory of Acceptance and Use of Technology model with financial literacy affects the behaviour of cryptocurrency investment.